AB0287 High Levels of 25(OH)D Are Associated with Lower Disease Activity in Patients with Newly Diagnosed Rheumatoid Arthritis. (9th June 2015) - Rasch, L.A.; Konijn, N.P.C.; Krul-Poel, Y.H.M.; van Tuyl, L.H.D.; Raterman, H.G.; Ter Wee, M.M.; den Uyl, D.; Simsek, S.; Nurmohamed, M.; Lems, W.F.
Abstract : Background: Vitamin D deficiency is highly common in patients with rheumatoid arthritis (RA) (1). In vitro, vitamin D has anti-inflammatory effects and vitamin D has been linked to disease activity in RA due to its immuno-modulatory properties (1, 2). Objectives: To investigate the association between vitamin D status and disease activity in newly diagnosed RA patients before start of therapy. Methods: Consecutive patients with active, newly diagnosed RA (symptom duration <2 years), were randomized for treatment with COBRA or COBRA-light therapy (3). Before start of therapy, baseline values were determined, including Disease Activity Score (44 joint; DAS) and serum 25-hydroxy vitamin D (25(OH)D) levels. Based on the widely used cut-off values, patients were stratified into three groups based on baseline serum 25(OH)D levels: <50 nmol/l, 50-74 nmol/l, and ≥75 nmol/l. Results: Baseline serum 25(OH)D levels were determined in 147 of 164 included RA patients in the COBRA-light trial (90% of trial population). Serum 25(OH)D levels of the different groups are presented in Table 1 . Patients with a baseline serum 25(OH)D level ≥75 nmol/l had a significant lower mean DAS compared to patients with a baseline serum 25(OH)D <75 nmol/l (p=0.001). Vitamin D deficient patients (<50 nmol/l) had a significant shorter symptom duration (p=0.003), and were more often rheumatoid factor positive (p=0.015) compared to patients with sufficient serum 25(OH)D levels. Conclusions: Newly diagnosed RA patients with serum 25(OH)D levels ≥75 nmol/l demonstrate a significant lower disease activity than patients with a serum 25(OH)D level <75 nmol/l before start of therapy. This study cannot distinguish whether a lower DAS at baseline is caused by immuno-modulatory properties due to higher serum 25(OH)D levels, or that higher serum 25(OH)D levels are caused by more frequent outdoor activities related to a lower DAS. Since 75% of the newly diagnosed RA patients have insufficient serum 25(OH)D levels (<75 nmol/l), vitamin D supplementation should be considered in every newly diagnosed RA patient. References: Grazio S, et al. Am J Med Sci 2014. Baker JF, et al. Clin Exp Rheumatol 2012. Den Uyl D, et al. Ann Rheum Dis 2013. Disclosure of Interest: L. Rasch: None declared, N. Konijn: None declared, Y. Krul-Poel: None declared, L. van Tuyl: None declared, H. Raterman: None declared, M. ter Wee: None declared, D. den Uyl: None declared, S. Simsek: None declared, M. Nurmohamed: None declared, W. Lems Grant/research support from: This research was performed within the framework of project T1-106 of the Dutch Top Institute Pharma, and was additionally funded by an unrestricted grant from Pfizer.